Evaluation of changes in vitamin B12, ferritin, folic acid, and thyroid hormone levels after sleeve gastrectomy (Annals of Medical Research, 2021)
None
Keywords: Thyroid-Stimulating Hormone; Vitamin B12; Ferritin; Gastrectomy.